Male involvement enhances the uptake of early infant diagnosis of HIV services in Thyolo, Malawi: A non-equivalent control group quasi-experimental study - Miriam Window; Alinane Linda Nyondo-Mipando; Noel Kalanga (PLoS ONE, 2023)
Background Poor retention of HIV-exposed infants (HEIs) in the Early Infant Diagnosis (EID) programme remains a significant challenge and impedes progress towards the elimination of Mother to Child Transmission (eMTCT). Suboptimal involvement of a father in his child’s participation in the EID of HIV services is one of the reasons for delayed initiation and poor retention in EID. This study compared the uptake of EID of HIV services at 6weeks from 6 months pre and post-implementation of the Partner invitation card and Attending to couples first (PA) strategy for male involvement (MI) at Bvumbwe Health Centre in Thyolo, Malawi. Methods We conducted a non-equivalent control group quasi-experimental study from September 2018 to August 2019 and enrolled 204 HIV positive women with HIV exposed infants who delivered at Bvumbwe health facility. 110 women were in the period before MI in EID of HIV services from September 2018 to February 2019 whereas 94 of them were in the period of MI in EID of HIV services from March to August 2019 receiving PA strategy for MI. Using descriptive and inferential analysis we compared the two groups of women. As age, parity and education levels of women were not associated with the uptake of EID, we proceeded to calculate unadjusted odds ratio. Results We observed an increase in the proportion of women that took up EID of HIV services such that 64/94 (68.1%) came for EID of HIV services at 6weeks from 44/110 (40%) in the period before MI. The uptake of EID of HIV services had an odds ratio of 3.2(95%CI: 1.8–5.7) P = 0.001) compared to the uptake of EID of HIV services before MI OR of 0.6(95%CI: 0.46–0.98) P = 0.037). Age, parity, and education levels of women were statistically insignificant. Conclusion The uptake of EID of HIV services at 6 weeks increased during the implementation of MI compared to the period before. Age, parity, and education levels of women were not associated with the EID uptake of HIV services at 6 weeks. Further studies on male involvement and uptake of EID should continue to be carried out to contribute to understanding of how high levels of EID uptake of HIV services can be achieved.